Results of the cystic and predominantly cystic thyroid nodules’ treatment by percutaneous ethanol injection - Lázaro Lorda Galiano; Jacinto Oscar Navas Igarza (Medisur)
Foundation: Cystic thyroid nodules, usually benign, can cause clinical symptoms. Percutaneous ethanol injection is recognized as first-line treatment for thyroid cysts and nodules with a predominant liquid component. Objective: To describe the results of the cystic and predominantly cystic thyroid nodules’ treatment by percutaneous ethanol injection. Methods: A descriptive study was conducted in patients with benign nodular goiter and cystic and predominantly cystic dominant nodules, treated with percutaneous ethanol injection. Categorical variables were described by absolute frequencies and percentages; and for the numerical ones the mean and standard deviation were calculated. The changes between the initial and final volumes of the nodules were evaluated using the Student t test for related samples. Results: 12 months after the treatment, the percentage reduction in the volume of the nodules behaved as follows: mean 92.50 ± 5.5 minimum 81.0 and maximum 99.8. Clinical success was complete in 100% of the patients, as was the efficacy of the technique. The only adverse effect was burning in 2 patients (8.33%). No patient presented complications during the study. Conclusions: Treatment with percutaneous ethanol injection in patients with nodular goiter and cystic or predominantly cystic dominant thyroid nodules is safe and effective, with transient adverse effects and a very low rate of complications.